Arsenic adsorption over dodecahedra ZIF-8 from solution aqueous: modelling, isotherms, kinetics and thermodynamics. Issue 4 (16th March 2022) - Massoudinejad, Mohamadreza; Mohammadi, Aliakbar; Sadeghi, Shahram; Ghaderpoori, Mansour; Sahebi, Soleyman; Alinejad, Abdolazim
ABSTRACT: Arsenic is one of the major pollutants in water resources which are highly toxic to consumers. Recently, a new class of adsorbents has been used to remove environmental pollutants such as Zeolite iImidazole Frameworks (ZIF-8). The aim of this study was to synthesise ZIF-8 and optimise for arsenic adsorption. The prepared ZIF-8 was characterised by FTIR, XRD, EDX, FE-SEM, and BET surface area. The ZIF-8 performance was assessed for variables such as initial arsenic concentration, pH, adsorbent dosage, and contact time. To measure the residual arsenic concentration, ICP-OES was used. Morphology of the synthesised ZIF-8 was dodecahedral. The particle size of synthesised ZIF-8 was in the range of 420 nm to 744 nm. The surface area of dodecahedral-ZIF-8 was 1566 m 2  g −1 . The study findings showed that experimental data could be well represented by the pseudo-second-order model and the Langmuir isotherm model. The arsenic adsorption on ZIF-8 was endothermic. The results of this study showed that ZIFs can be used to remove environmental pollutants effectively.